INVENTORY OF EPIPHYTIC LICHENES ON MANGO (MANGIFERA INDICA L.) IN SALLU VILLAGE, DISTRICT WEST MIOMAFFO - -, Kamaluddin; GUMELAR, ASEP IKHSAN; PRIYAMBODO, HERNUR YOGA (Agroprimatech, 2023)
Lichenes are formed from the association of fungi and phostosynthetic symbionts (algae and cyanobacteria) by forming a stable thallus structure. The aim of this research is to determine the diversity of epiphytic lichens on mango trees in Sallu Village, West Miomaffo District in March-May 2023. This research uses an exploratory method on mango plantations. The sampling method uses purposive sampling. Based on exploration results, 33 species of epiphytic lichens were found on mango trees in Sallu Village, West Miomaffo District. The Lichenes species found consist of 14 families, namely Parmeliaceae, Physciaceae, Graphidaceae, Pannariaceae, Caliciaceae, Collemataceae, Lecanoraceae, Stereocaulaceae, Pertusariaceae, Mycoporaceae, Pyrenulaceae, Haematommataceae, Arthoniaceae, and Ochrolechiaceae.